2014
DOI: 10.1128/iai.02537-14
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma marginale Superinfection Attributable to Pathogen Strains with Distinct Genomic Backgrounds

Abstract: Strain superinfection occurs when a second pathogen strain infects a host already infected with a primary strain. The selective pressures that drive strain divergence, which underlies superinfection, and allow penetration of a new strain into a host population are critical knowledge gaps relevant to shifts in infectious disease epidemiology. In regions of endemicity with a high prevalence of infection, broad population immunity develops against Anaplasma marginale, a highly antigenically variant rickettsial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…The occurrence of superinfection exclusion and the failure to transmit the second strain following sequential exposure are consistent with a previous study using genetically distinct Virginia and Oklahoma strains in adult male Dermacentor variabilis ticks (17). This confirmation of superinfection exclusion within a short time window is in agreement with populationbased studies of A. marginale strain structure (2,6). Vallejo Esquerra et al reported that infected cattle, a natural host for A. marginale, in tropical regions of Mexico carried multiple strains (mean of 3.3 Ϯ 1.2 strains per animal), with up to six strains detected in an individual (2).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The occurrence of superinfection exclusion and the failure to transmit the second strain following sequential exposure are consistent with a previous study using genetically distinct Virginia and Oklahoma strains in adult male Dermacentor variabilis ticks (17). This confirmation of superinfection exclusion within a short time window is in agreement with populationbased studies of A. marginale strain structure (2,6). Vallejo Esquerra et al reported that infected cattle, a natural host for A. marginale, in tropical regions of Mexico carried multiple strains (mean of 3.3 Ϯ 1.2 strains per animal), with up to six strains detected in an individual (2).…”
Section: Discussionsupporting
confidence: 80%
“…Individual hosts in tropical regions, characterized by long periods of warm temperatures and high relative humidity, carry multiple genetically distinct A. marginale strains, and there is broad hetero geneity at the population level (2,6,24). In contrast, hosts in temperate regions are most commonly infected with only a single A. marginale strain, and the overall population strain structure is homogeneous (25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even a single unique msp2 allele is sufficient to allow strain superinfection, with the requirement that the unique allele be expressed at the time of superinfection (10). Within regions of endemicity with high population immunity against a dominant strain, there is strong selective pressure for emergence of new strains, and consequently, strain superinfection is common (12,21,24,27). While there is genomic evidence that a new strain may emerge by insertions or deletions within a previously duplicated msp2 allele, the magnitude of change in the Msp2 primary structure required to generate a truly antigenically unique strain capable of superinfection is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Segmental gene conversion uses combinatorial recombination to generate hundreds to thousands of novel sequence variants not represented elsewhere in the genome other than transiently in the expression site (9). For this expansion to be functional in pathogen persistence requires that they evade the extant antibody response (12,21,22). The fraction of structural variants that represent antigenic variants has been unknown.…”
Section: Discussionmentioning
confidence: 99%